Ecological Surveillance for West Nile in Catalonia (Spain), Learning from a Five‐Year Period of Follow‐up. (17th April 2013) - Alba, A.; Allepuz, A.; Napp, S.; Soler, M.; Selga, I.; Aranda, C.; Casal, J.; Pages, N.; Hayes, E. B.; Busquets, N.
Summary To enhance early detection of West Nile virus (WNV) transmission, an integrated ecological surveillance system was implemented in Catalonia (north‐eastern Spain) from 2007 to 2011. This system incorporated passive and active equine surveillance, periodical testing of chicken sentinels in wetland areas, serosurveillance wild birds and testing of adult mosquitoes. Samples from 298 equines, 100 sentinel chickens, 1086 wild birds and 39 599 mosquitoes were analysed. During these 5 years, no acute WNV infection was detected in humans or domestic animal populations in Catalonia. WNV was not detected in mosquitoes either. Nevertheless, several seroconversions in resident and migrant wild birds indicate that local WNV or other closely related flaviviruses transmission was occurring among bird populations. These data indicate that bird and mosquito surveillance can detect otherwise silent transmission of flaviviruses and give some insights regarding possible avian hosts and vectors in a European setting.